Conceptualising historical literacy – a review of the literature (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
In a context of a continually widening range of disciplines and subjects available for learners to specialize in, it becomes increasingly critical for the value of particular subjects to be examined. Thus, while debates rage over the relevance and worth of school history, we contribute to the conceptualization of what school history is for. In other words, we examine what history learners acquire as a result of studying the subject. We argue that learners gain a certain form of historical literacy which cannot always be generalized to different contexts. As such, the historical literacy that learners gain varies according to context, place and time. In this article we specifically review literature related to the functional realm of History Education and, particularly, historical literacy. We then construct benchmarks of historical literacy as informed by the literature. This research thus avails a foundation for further empirical research on the purpose of school history.
Keywords: History; Historical literacy; Conceptual understanding; Historical consciousness; Historical language; History education